Stereographic projection for territory of the Republic of Macedonia - Zlatko Srbinoski; Zlatko Bogdanovski; Filip Kasapovski; Tome Geogovski (Faculty of civil engineering - Skopje, 2018)
In stereographic projection, as one of the oldest cartographic projections, Earth is approximate with sphere in the first step and then it is projected on the tangent or cutting plane. The famous Bulgarian geodetic scientist Prof. Vladimir Hristov Ph.D made stereographic projection with direct projecting of ellipsoid on plane. In this work, basically postulate for composing of stereographic for territory of R. of Macedonia are defined.
Keywords: stereographic projection, linear deformations